‘At school I got myself a certificate’: HIV/AIDS Orphanhood and Secondary Education: a Qualitative Study of Risk and Protective Factors - Watkins, J.; Sello, O.; Cluver, L.; Kaplan, L.; Boyes, Mark (Springer, 2014)
Secondary school is a period during which risk of school dropout is highest. To date, little research has examined reasons for school dropout amongst HIV/AIDS-orphaned children, who are affected economically, psychosocially and educationally. HIV/AIDS orphanhood can perpetuate poverty and increase school dropout in a range of ways, including inability to pay school fees, family disruption and stigma. Related research mostly focuses on school performance and completion and, more recently, on context-specific approaches to measure educational outcomes. The primary aim of this qualitative study was to examine how HIV/AIDS orphanhood influences participation in secondary education in South Africa and to investigate why some HIV/AIDS-orphaned adolescents find it easier to stay in school than others. Specifically, the study aimed to explore, interpret and elicit the perceptions of South African HIV/AIDS-orphaned adolescents (N = 243, aged 13–22, 53 % female, 47 % male) towards potential risk and protective factors influencing their secondary school attendance. Findings suggest complex and interconnecting multiple risk factors such as poverty pre- and post-parental death, crisis-fosterage often accompanied by further traumatic events, changing schools sporadically, recurring household migration and forced employment all of which can create obstacles to secondary education. Protective factors that emerged included extra-curricular activities and teacher/community support. These findings highlight the need for evidence-informed school and community policies, which consider the effects of household poverty, migration and living arrangements, if secondary school participation for HIV/AIDS-orphaned adolescents is to be promoted and sustained.